Enhanced interferon regulatory factor 3 binding to the interleukin-23p19 promoter correlates with enhanced interleukin-23 expression in systemic lupus erythematosus - Smith, Siobhán; Gabhann, Joan Nı´; Higgs, Rowan; Stacey, Kevin; Wahren-Herlenius, Marie; Espinosa, Alexander; Totaro, Maria Grazia; Sica, Antonio; Ball, Elizabeth; Bell, Aubrey; Johnston, James; Browne, Peter; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To examine the role of interferon regulatory factor 3 (IRF‐3) in the regulation of interleukin‐23 (IL‐23) production in patients with systemic lupus erythematosus (SLE). Methods Bone marrow–derived macrophages were isolated from both wild‐type and IRF3−/− C57BL/6 mice. These cells were stimulated with the Toll‐like receptor 3 (TLR‐3) agonist poly(I‐C), and IL‐23p19 cytokine levels were analyzed by enzyme‐linked immunosorbent assay. IRF‐3 binding to the IL‐23p19 gene promoter region in monocytes from patients with SLE and healthy control subjects was analyzed by chromatin immunoprecipitation (ChIP) assay. Luciferase reporter gene assays were performed to identify key drivers of IL‐23p19 promoter activity. TANK‐binding kinase 1 (TBK‐1) protein levels were determined by Western blotting. Results ChIP assays demonstrated that IRF‐3 was stably bound to the human IL‐23p19 promoter in monocytes; this association increased following TLR‐3 stimulation. Patients with SLE demonstrated increased levels of IRF‐3 bound to the IL‐23p19 promoter compared with control subjects, which correlated with enhanced IL‐23p19 production in monocytes from patients with SLE. Investigations of the TLR‐3–driven responses in monocytes from patients with SLE revealed that TBK‐1, which is critical for regulating IRF‐3 activity, was hyperactivated in both resting and TLR‐3–stimulated cells. Conclusion Our results demonstrate for the first time that patients with SLE display enhanced IL‐23p19 expression as a result of hyperactivation of TBK‐1, resulting in increased binding of IRF‐3 to the promoter. These findings provide novel insights into the molecular pathogenesis of SLE and the potential role for TLR‐3 in driving this response.